Front Cover: Exosomes as a Source of Cancer Biomarkers: Advances in Electrochemical Biosensing of Exosomes (ChemElectroChem 9/2020). Issue 9 (8th April 2020) - Lorencova, Lenka; Bertok, Tomas; Bertokova, Aniko; Gajdosova, Veronika; Hroncekova, Stefania; Vikartovska, Alica; Kasak, Peter; Tkac, Jan
Abstract : The Front Cover illustrates a common eukaryotic cell with basic organelles, as well as intracellular formation/preparation of exosomes for express delivery to distant tissues. More information can be found in the Review by L. Lorencova et al .